$\phantom{\rule{2.77695pt}{0ex}}\phantom{\rule{2.77695pt}{0ex}}\frac{1}{2}-\frac{1}{3}+\frac{1}{4}-\frac{2}{5}$ ]]> $\frac{1}{30}$ ]]>$\frac{1}{120}$ ]]>$\frac{1}{60}$ ]]>$-\frac{1}{60}$ ]]>$-\frac{1}{30}$ ]]> $\phantom{\rule{2.77695pt}{0ex}}\phantom{\rule{2.77695pt}{0ex}}\frac{\sqrt{5}+1}{\sqrt{5}-1}$ ]]> $\frac{3+\sqrt{5}}{2}$ ]]>$\frac{3-\sqrt{5}}{2}$ ]]>$\frac{\sqrt{5}-3}{2}$ ]]>$\frac{6+\sqrt{5}}{2}$ ]]>$\frac{6-\sqrt{5}}{2}$ ]]> $xy\phantom{\rule{2.77695pt}{0ex}}$-plane is ]]> $y=3x-1$ ]]>$y=5x-3$ ]]>$y=3x+1$ ]]>$y=4x-1$ ]]>$y=4x-2$ ]]> $2{x}^{2}+7x-15\phantom{\rule{2.77695pt}{0ex}}\phantom{\rule{2.77695pt}{0ex}}\phantom{\rule{2.77695pt}{0ex}}\phantom{\rule{2.77695pt}{0ex}}\phantom{\rule{2.77695pt}{0ex}}$ factorises as ]]> $\left(2x+3\right)\left(x-5\right)$ ]]>$\left(2x-5\right)\left(x+3\right)$ ]]>$\left(2x-5\right)\left(x-3\right)$ ]]>$\left(2x+5\right)\left(x-3\right)$ ]]>$\left(2x-3\right)\left(x+5\right)$ ]]> $\phantom{\rule{2.77695pt}{0ex}}\phantom{\rule{2.77695pt}{0ex}}\phantom{\rule{2.77695pt}{0ex}}\phantom{\rule{2.77695pt}{0ex}}30{0}^{\circ }$ ]]> $\frac{3\pi }{2}$ ]]>$\frac{2\pi }{3}$ ]]>$\frac{5\pi }{3}$ ]]>$\frac{5\pi }{6}$ ]]>$\frac{4\pi }{3}$ ]]> Which of the following functions describes the above graph? ]]> $y=-{\left(x-1\right)}^{2}+2$ ]]>$y=2x\left(2-x\right)$ ]]>$y=-2{\left(x+1\right)}^{2}+2$ ]]>$y=2{\left(x-1\right)}^{2}+2$ ]]>$y=x\left(2-x\right)$ ]]> ${e}^{2x}{e}^{5{x}^{2}}$ ]]> ${e}^{7{x}^{2}}$ ]]>${e}^{10{x}^{3}}$ ]]>${e}^{x\left(2+5x\right)}$ ]]>${e}^{2x}+{e}^{5{x}^{2}}$ ]]>${e}^{10x\left(1+x\right)}$ ]]> $\phantom{\rule{1em}{0ex}}ln\left(\frac{a{b}^{3}}{{c}^{2}}\right)$ ]]> $lna+ln3b-ln2c$ ]]>$lna+3lnb-2lnc$ ]]>$3lnab-2lnc$ ]]>$3lnab-ln2c$ ]]>$lna-3lnb+2lnc$ ]]> $\phantom{\rule{2.77695pt}{0ex}}\phantom{\rule{2.77695pt}{0ex}}tan\left(5\pi ∕6\right)$ ]]> $\sqrt{3}$ ]]>$-\sqrt{3}$ ]]>$-\frac{1}{\sqrt{3}}$ ]]>$\frac{1}{\sqrt{3}}$ ]]>$-1$ ]]> $x$ for the following equation: $\phantom{\rule{2.77695pt}{0ex}}\phantom{\rule{2.77695pt}{0ex}}\phantom{\rule{2.77695pt}{0ex}}\phantom{\rule{2.77695pt}{0ex}}\frac{1}{x-1}+\frac{1}{x+3}=2$ ]]> $x=\frac{1±\sqrt{17}}{2}$ ]]>$x=\frac{-1±\sqrt{17}}{2}$ ]]>$x=±\sqrt{5}$ ]]>$x=±2$ ]]>$x=2$ ]]>